Genome-wide identification, tissue expression pattern, and salt stress response analysis of the NAC gene family in Thinopyrum elongatum - Jilin Sun; Xiaokuo Cui; Jiaqi Zhang; Fansen Meng; Jiangong Li; Shenghui Zhou; Changai Wu; Peng Zhou; Silong Sun; Long Han (BMC Plant Biology)
Abstract Background The NAC (NAM, ATAF1/2, and CUC2) gene family plays a critical role in regulating plant growth, developmental processes, and stress response mechanisms. While NAC genes have been systematically characterized in multiple plant species, this study focused on genome-wide identification of NAC family members in Thinopyrum elongatum (designated as TeNACs) through integrated bioinformatics approaches. Comprehensive analyses were conducted to determine the physicochemical characteristics, conserved motifs, gene structure, phylogenetic relationships, chromosomal collinearity, and expression profiles of the identified TeNACs. This multi-dimensional characterization provides fundamental insights into the structural and functional diversity of NAC transcription factors in Th. elongatum. Results A total of 116 NAC transcription factors were systematically identified in Th. elongatum, distributed across all seven chromosomes. Comprehensive physicochemical characterization revealed substantial variation among TeNAC proteins: amino acid length (162–718 aa), molecular weight (18.33–78.25 kDa), isoelectric point (6.5–7.5), instability index (30.34–63.32), and aliphatic index (50.92–80.68). Hydropathicity analysis confirmed the hydrophilic nature of all TeNACs, with grand average values consistently below zero. Conserved motif profiling demonstrated a highly conserved architecture in TeNACs, featuring ordered arrangements of motifs 3, 4, 1, 5, 6, 2, and 7. Phylogenetic reconstruction classified TeNACs into 14 distinct clades through comparative analysis with Arabidopsis thaliana NAC genes, notably lacking ANAC001 and OsNAC8 homologs. Comparative genomic analysis identified significant syntenic conservation between TeNACs and wheat NAC genes. Protein interaction network prediction indicated intricate functional associations among TeNAC proteins. Computational predictions coupled with experimental validation of TeNAC021 confirmed exclusive nuclear localization for all family members. Differential expression analysis across a salt gradient (0–300 mM) identified 14 TeNACs with progressive up-regulation and 5 showing consistent down-regulation. RT-qPCR confirmed salt-responsive expression patterns for eight TeNACs demonstrating marked transcriptional changes. Conclusions This systematic investigation establishes a robust theoretical framework for subsequent structural and functional characterization of TeNACs in Th. elongatum.